An observation of words that mimic animal sounds in the Mongolian and Korean - B, Purevsan (Mongolian Language and Literature Studies, 2024)
The sounds of objects and phenomena in the real world are expressed in language using onomatopoeic words. In this process, each language represents a specific natural sound differently, which is closely related to how the sound is perceived and experienced. For example, the sound of a dog barking is expressed as “хав хав” in Mongolian, “гав гав” in Russian, “わんわん [wan wan]” in Japanese, and “멍멍 [meong meong]” in Korean. Onomatopoeic words are among the first words children learn and share char acteristics similar to early language acquisition patterns. Therefore, young children frequently use onomatopoeic words, and it is common for them to name animals based on the sounds they make. Based on the Mongolian explanatory dictionary and onomatopoeic word dictionary, I have analyzed and organized how animal sounds are represented using onomatopoeic words in the Mongolian language. Additionally, during this research process, I observed how animal sounds are expressed in the Korean language, analyzing their structure, types, and unique characteristics. In Mongolian, onomatopoeic words representing animal sounds appear in either singular or repeated forms. These words not only indicate a single sound or a continuous sound made by the animal, but they also have the feature of switching between different sounds to represent various sources of the sound. Additionally, in Mongolian, onomatopoeic words can form verbs by adding verb suffixes to represent animal sounds. In contrast, the representation of animal sounds in Korean is less frequent compared to Mongolian, and when used, it is often in the form of repeated onomatopoeic words to express animal sounds. Монгол, Солонгос хэлний амьтдын дуугарах дуу авианы нэрийн ажиглалт Хураангуй Бодит ертөнцийн юмс, үзэгдлийн дуу авиаг хэлэнд авиа дуурайх үгээр дуурайн тэмдэглэдэг. Ингэж тэмдэглэхдээ байгалийн тодорхой нэг дуу авиаг хэл бүрд янз бүрээр тэмдэглэдэг ба энэ нь тухайн дуу авиаг хэрхэн сонсож мэдэрсэнтэй үлэмж холбоотой юм․ Жишээлбэл: нохой хуцах дууг монгол хэлэнд “хав хав”, орос хэлэнд “гав гав”, япон хэлэнд “わんわん[wanwan]”, солонгос хэлэнд “멍멍 [meongmeong]” гэх мэт․ Авиа дуурайх үг нь хүүхдийн анх сурах үг, түүний хэлбэр бүтэцтэй адилхан байдаг. Тиймээс бага насны хүүхдүүд авиа дуурайх үгийг их хэрэглэдэг төдийгүй ан амьтдын нэрийг тэдгээрийн дуугарах дуу авиагаар нь нэрлэх явдал ажиглагддаг. Монгол хэлэнд амьтдын дуугарах дуу авиаг авиа дуурайх үгээр хэрхэн тэмдэглэдэг болохыг тус хэлний тайлбар толь, дуурайх үгийн тольд тулгуурлан шүүн түүвэрлэж тэдгээрийн бүтэц, хэв шинж, онцлогийг судлах явцдаа солонгос хэлэнд амьтдын дуу авианы нэрийг хэрхэн тэмдэглэдэг болохыг мөн ажигласан болно. Амьтдын дуу авиаг дуурайн тэмдэглэсэн авиа дуурайх үг монгол хэлэнд дан буюу давтсан хэлбэрээр орж тухайн амьтны нэг удаагийн болон удаан үргэлжлэх дуу авиаг илтгэхээс гадна дуу авиа үүсгэгч эзэн олон буйг авиа сэлгэн илэрхийлдэг онцлогтой байна. Мөн авиа дуурайх язгуур дээр үйл үг бүтээх дагавар залган амьтдын дуугарах дуу авиаг үйл үгээр илэрхийлдэг онцлогтой байхад солонгос хэлэнд амьтдын дуу авиаг тэмдэглэх нь монгол хэлтэй харьцуулахад бага байгаа бөгөөд, ингэхдээ давтсан бүтэцтэй авиа дуурайх үгээр амьтдын дуу авиаг ихэвчлэн дуурайн тэмдэглэдэг болох нь ажиглагдлаа. Түлхүүр үг: ан гөрөөсний, шувууны, мал, тэжээмэл амьтны, жижиг амьтны дуу авиа, монгол, солонгос хэлний авиа дуурайх үг